Randwanderung, Pendeln und Geschlecht in einer polyzentralen Region - Scheiner, Joachim (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
The paper studies commute distances and commute duration in the context of suburbanisation and gender relations in the surroundings of Hagen, Westphalia. The results show that intraregional migration is often motivated by workplace-related reasons. The gender-specific changes in commuting following the moves suggest that residential location choice tends to be driven by the male partner’s workplace, while women hold a “trailing wife” position. Additionally, the moves are associated with attempts to limit or reduce commuting trip lengths on the household level. This is not only reflected in trip duration, but also in the spatial configuration of housing and work among employed couples. This is represented here by the relative location of the residence and workplaces. In a ring of 20–30 km around Hagen the residential choices are associated with considerably longer commuting distances, compared to municipalities located closer to Hagen (
Keywords: Suburbanisation; Commuting; Gender; Residential location choice; Polycentric region